Diversification entry: Internal development versus acquisition - Yip, George S. (Strategic Management Journal, 1982)
Abstract The economic theory of barriers to entry is integrated with the corporate strategy concept of relatedness, to develop a model of the choice between internal development and acquisition in diversification entry into new markets. The model is tested on original data collected for this study from PIMS Program participants. These original data cover the parent company characteristics, entry strategy and entry outcome for 59 entrants into 31 markets. These entry‐related data are merged with existing PIMS data on the structure of the entered markets and their incumbents. Results of binary regression analysis show that the choice between the two entry modes is well explained by measures of barriers and relatedness. Higher barriers are more likely to be associated with acquisition entry. Greater relatedness is more likely to be associated with direct entry.